2017
DOI: 10.3892/mmr.2017.6577
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the mouse brain exposed to chronic mild stress: The influence of hepatocyte nuclear factor 4α on physiological homeostasis

Abstract: Major depressive disorder (MDD) is a prevalent disorder that causes considerable disability in social functioning and is a risk factor for physical diseases. Recent clinical reports have demonstrated a marked association between MDD and physiological dyshomeostasis induced by metabolic disorders, including diabetes, hormone abnormalities and autoimmune diseases. The authors of the present study have previously analyzed comparative gene expression profiles in the prefrontal cortex (PFC) of a chronic mild stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…RT-qPCR showed that mRNA expression decreased significantly for 16 of 18 molecules in Il18 −/− mice. In our previous study [ 25 ], we proposed that Ahsg and S100 calcium binding protein A9 ( S100a9 ) were key mediators not only of depression but also of physiological dysregulation, for example, diabetes mellitus. Additionally, Ttr was suggested to be an inducer of MDD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RT-qPCR showed that mRNA expression decreased significantly for 16 of 18 molecules in Il18 −/− mice. In our previous study [ 25 ], we proposed that Ahsg and S100 calcium binding protein A9 ( S100a9 ) were key mediators not only of depression but also of physiological dysregulation, for example, diabetes mellitus. Additionally, Ttr was suggested to be an inducer of MDD.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, higher AHSG was reported in male MDD patients compared with controls [ 52 ]. While AHSG expression in the PFC, but not the thalamus and hippocampus, was increased in our depressive model mice, its expression in Il18 −/− mice was unchanged [ 25 ] ( Figure 3(b) ). Thus, these results suggest that AHSG is a key factor connecting depression, energy homeostasis, and the immune system in IL-18 deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, S100a9 expression has been found in AD patients and genetically modified AD animal models, suggesting that S100a9 expression may be involved in the pathology of AD [ 13 ]. It has been reported that S100a9 is also expressed in animal models of major depressive disorder [ 16 ] and is significantly higher in the dorsolateral prefrontal cortex of schizophrenia patients [ 9 ], suggesting that S100a9 is associated not only with dementia but also with psychiatric disorders such as depression. Although SDT fatty rats are hyperglycemic and obese models and thus may be exposed to chronic inflammation and stress, no increase in TNF-α or HSP70 was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding RNA purification, microarray analysis, RT-qPCR, and IPA (Ingenuity ® Systems; ingenuity.com) have been described in our previous studies (15)(16)(17).…”
Section: Methodsmentioning
confidence: 99%